Sprachstrukturen der Konzepte „Wende“ in den Diskursen der modernen deutschen Sprache. Language structures of “Turn” Concepts in the discourses of modern German language - Kovtyk, Bogdan (Glottodidactica, 2012)
German language structures analysis of „turn“-concepts is interconnected with the term concept itself on the one side and with the discourses of “turn” on the other side. Furthermore there is a deep need to research the concepts and conceptuality of German language structures of “turn” according to the newest findings of lexicography, communication studies and information linguistics, allowing the precise comparison within several similar discourses of “turn”. Finally, the concept items of “turn” will be comprehensively described and illustrated using online analyses of “turn” structures in narrative and argumentative situations.